Neurocysticercosis: HP10 antigen detection is useful for the follow-up of the severe patients - Fleury, Agnès (2013)
The most severe clinical form of neurocysticercosis (NC) occurs when cysticerci are located in the subarachnoid space at the base of the brain (SaB). The diagnosis, monitoring and treatment of NC-SaB, constitutes a severe clinical challenge. Herein we evaluate the potential of the HP10 antigen detection enzyme-linked immunosorbent assay (HP10 Ag-ELISA) in the long term follow-up of NC-SaB cases. Assay performance was compared with that of Magnetic Resonance Imaging (MRI). In addition, the robustness of the HP10 Ag-ELISA was evaluated independently at two different institutions.